Immigration and Employment : Substitute Versus Complementary Labor in Selected African Countries - Viseth, Arina (Washington, D.C. : International Monetary Fund, 2020)
This paper uses census and household survey data on Cameroon, Ghana, and South Africa to examine immigration's impact in the context of a segmented labor market in Sub-Saharan Africa. We find that immigration affects (i) employment (ii) employment allocation between informal and formal sectors, and (iii) the type of employment within each sector. The direction of the impact depends on the degree of complementarity between immigrants and native workers' skills. Immigration is found to be productivity-enhancing in the short to near term in countries where, the degree of complementarity between immigrants and native workers' skill sets is the highest.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet